Do protagonismo judicial ao diálogo institucional: os meios de resolução alternativa de conflitos como instrumentos à desjudicializaçãp da saúde. - Prazeres, Paulo Joviniano Álvares dos (2022)
Although a vast academic production on the phenomenon of judicialization can be verified, the theme still encompasses numerous controversies and a solution is pending. The growing judicialization correlates with the fact that the Judiciary is now required to decide on the compatibility of commissive and omissive acts of state power. In this sense, the present study will analyze decisions of general repercussion issued by the STF and if it is possible to verify the existence of parameters regarding the judicialization of health, and, through a partially comparative analysis, the work will also observe emblematic decisions of the Colombian Court and of South Africa, and how each of these countries deals with this phenomenon. As an alternative to the growing judicialization, the work will cover the importance of institutional dialogues and the possibility of resolving conflicts in the health area, through alternative methods of conflict resolution. In this way, it will be possible to demonstrate, through practical cases that are in progress in several Brazilian states, the success of alternative means of conflict resolution in the health area, in order to provide greater effectiveness of this constitutional guarantee, in addition to reducing public spending and curb judicialization. The research uses the method of systematic literature review, as it corresponds to the use of several literature reviews to efficiently integrate and analyze a large amount of information, enabling a more effective decision/conclusion.